Near-InfraRed PhotoImmunoTherapy (NIR-PIT) for the local control of solid cancers: Challenges and potentials for human applications. (May 2021) - Paraboschi, Irene; Turnock, Stephen; Kramer-Marek, Gabriela; Musleh, Layla; Barisa, Marta; Anderson, John; Giuliani, Stefano
Graphical abstract: Highlights: Near-InfraRed PhotoImmunoTherapy (NIR-PIT) is a promising technique aiming to selectively kill cancer cells while leaving the host tissues and organs undamaged. It is effected by a chemical conjugation between a photosensitiser ( e.g. the NIR phthalocyanine dye IRDye700DX) and a cancer-targeting moiety ( e.g. a monoclonal antibody, moAb). Preclinical and clinical studies of NIR-PIT in a variety of cancers are here brought together highlighting the key unanswered research questions. Abstract: Near-InfraRed PhotoImmunoTherapy (NIR-PIT) is a novel cancer-targeted treatment effected by a chemical conjugation between a photosensitiser ( e.g. the NIR phthalocyanine dye IRDye700DX) and a cancer-targeting moiety ( e.g. a monoclonal antibody, moAb). Delivery of a conjugate in vivo leads to accumulation at the tumour cell surface by binding to cell surface receptors or antigens. Upon deployment of focal NIR-light, irradiation of the conjugate results in a rapid, targeted cell death. However, the mechanisms of action to produce the cytotoxic effects have yet to be fully understood. Herein, we bring together the current knowledge of NIR-PIT from preclinical and clinical studies in a variety of cancers highlighting the key unanswered research questions. Furthermore, we discuss how to enhance the local control of solid cancers using this novel treatment regimen.